3D CFD-DEM simulation and experiment on proppant particle-fluid flow in a vertical, nonplanar fracture with bends. (January 2022) - Qu, Hai; Liu, Ying; Lin, Hun; Tang, Shimao; Wang, Rui; Xue, Ling; Hu, Yushuang
Highlights: The particle-fluid flow in a nonplanar fracture is presented by the experiment and 3D CFD-DEM simulation. The CFD-DEM model is validated and calibrated against experimental data. The effects of key injection paramerters on particle transport and distribution are investigated. A regression model is developed for the coverage percentage of the particle bed. Abstract: Particle-fluid flow in complex fractures plays a crucial role in the stimulation of unconventional reservoirs. In this paper, particle transport experiments were conducted in a vertical, nonplanar slot with two 90° bends and a straight slot. The corresponding simulation model was performed by a 3D coupled method of computational fluid dynamics (CFD) and discrete element method (DEM), which was calibrated and validated against experimental results. The effects of bending angle, fluid velocity and viscosity, particle density on particle placement are analyzed based on the experimental and simulation results. The studies reveal that the particle-fluid flow pattern is more complicated in the nonplanar slot than that of the straight slot. An irregular particle bed with two depressions around two bends would be formed. With the reduction of bending angle, the particle bed height and covered area decrease, while the sizes of the two depressions increase. The complicated flow induced by the bend increases the fluidization layer height. The high fluid velocity and viscosity can effectively suspend the low-density particles through two bends deeper into the complex fracture. A regression model with dimensionless numbers is developed for predicting the percentage of covered area. This study provides fundamental insight into understanding particle-fluid flow in a nonplanar fracture.